Optimizing Natural Resources: Dye Plant Conservation For the Harungguan Muara Ulos Weaving Industry - Dahlia Nopelina Siallagan; Rina Handayani; Sariayu Sibarani (International Journal of Information Technology and Business, 2024)
Plant dyes are used in the Harungguan Muara ulos weaving industry to optimize local natural resources. Synthetic dyes have become a fast option along with the increasing demand for ulos. However, synthetic dyes adversely affect the quality and sustainability of the environment. This research used observational methods, in-depth interviews, also gaining an understanding of current and applicable conservation practices. The research showed some local plant species are well suited to be used as a source of natural dyes, but their populations are threatened by overexploitation, lack of conservation efforts and emphasized the importance of traditional knowledge with contemporary conservation methods. The proposed recommendations educate ulos weavers on the importance of using natural dyes, and conduct follow-up research to find more efficient cultivation methods.This research make efforts to preserve Batak cultural heritage and support sustainability to strengthen the ulos weaving industry as an environmentally friendly and economically valuable cultural product.